Experimental Study on the Variation Law of Excess Pore Water Pressure at the Bottom of the Foundation Pit for Excavation - Qizhi Hu; Qiang Zou; Zhigang Ding; Zhaodong Xu (Advances in Materials Science and Engineering)
The excavation unloading of deep foundation pits in soft soil areas often produces negative excess pore water pressure. The rebound deformation of soil on the excavation surface of the foundation pit can be predicted reliably through the accurate expression of relevant variation laws. In combination with the principle of effective stress and the general equation of unidirectional seepage consolidation, an equation for calculating the rebound deformation from the bottom in the process of foundation pit excavation unloading was obtained. Additionally, a triaxial unloading test was adopted to simulate the excavation unloading processes for actual foundation pit engineering. After studying the variation law of the excess pore water pressure generated by excavation unloading, it was found that the negative excess pore water pressure increased with increasing unloading rate, while the corresponding peak value decreased with increasing confining pressure. The equation for rebound calculation was verified through a comparison with relevant measured data from actual engineering. Therefore, it is considered that the equation can reliably describe the rebound deformation law of the base. This paper aims to guide the design and construction of deep foundation pits in soft soil areas.